Comparison of Variational and Fractional Variational Iteration Methods in Solving Time-Fractional Differential Equations (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
This paper concerned with study of vartional iteration method(VIM) and fractional variational iteration method (FVIM) to solve time fractional  differential equations (FDE's) . So FVIM is more effective than VIM in solving the FDE's.